Soft Computing for Recognition Based on Biometrics - Melin, Patricia; Kacprzyk, Janusz; Pedrycz, Witold; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
We describe in this book, bio-inspired models and applications of hybrid intelligent systems using soft computing techniques for image analysis and pattern recognition based on biometrics and other information sources. Soft Computing (SC) consists of several intelligent computing paradigms, including fuzzy logic, neural networks, and bio-inspired optimization algo-rithms, which can be used to produce powerful hybrid intelligent systems. The book is organized in five main parts, which contain a group of papers around a similar subject.
Classification Algorithms and Applications -- Soft Computing Approaches to the Problem of Infant Cry Classification with Diagnostic Purposes -- Neural Networks and SVM-Based Classification of Leukocytes Using the Morphological Pattern Spectrum -- Hybrid System for Cardiac Arrhythmia Classification with Fuzzy K-Nearest Neighbors and Neural Networks Combined by a Fuzzy Inference System -- A Comparative Study of Blog Comments Spam Filtering with Machine Learning Techniques -- Distributed Implementation of an Intelligent Data Classifier -- Pattern Recognition -- Modular Neural Network with Fuzzy Integration and Its Optimization Using Genetic Algorithms for Human Recognition Based on Iris, Ear and Voice Biometrics -- Comparative Study of Type-2 Fuzzy Inference System Optimization Based on the Uncertainty of Membership Functions -- Modular Neural Network for Human Recognition from Ear Images Using Wavelets -- Modular Neural Networks for Person Recognition Using the Contour Segmentation of the Human Iris Biometric Measurement -- Real Time Face Identification Using a Neural Network Approach -- Comparative Study of Feature Extraction Methods of Fuzzy Logic Type 1 and Type-2 for Pattern Recognition System Based on the Mean Pixels -- Optimization Methods -- Application of the Bee Swarm Optimization BSO to the Knapsack Problem -- An Approach Based on Neural Networks for Gas Lift Optimization -- A New Evolutionary Method with Particle Swarm Optimization and Genetic Algorithms Using Fuzzy Systems to Dynamically Parameter Adaptation -- Local Survival Rule for Steer an Adaptive Ant-Colony Algorithm in Complex Systems -- Using Consecutive Swaps to Explore the Insertion Neighborhood in Tabu Search Solution of the Linear Ordering Problem -- A New Optimization Method Based on a Paradigm Inspired by Nature -- Theory and Algorithms -- Improvement of the Backpropagation Algorithm Using (1+1) Evolutionary Strategies -- Parallel Genetic Algorithms for Architecture Optimization of Neural Networks for Pattern Recognition -- Scene Recognition Based on Fusion of Color and Corner Features -- Improved Tabu Solution for the Robust Capacitated International Sourcing Problem (RoCIS) -- Variable Length Number Chains Generation without Repetitions -- Comparative Analysis of Hybrid Techniques for an Ant Colony System Algorithm Applied to Solve a Real-World Transportation Problem -- Computer Vision Applications -- Comparison of Fuzzy Edge Detectors Based on the Image Recognition Rate as Performance Index Calculated with Neural Networks -- Intelligent Method for Contrast Enhancement in Digital Video -- Method for Obstacle Detection and Map Reconfiguration in Wheeled Mobile Robotics -- Automatic Dust Storm Detection Based on Supervised Classification of Multispectral Data.
Keywords: Engineering; Artificial intelligence; Biometrics; Engineering design; Engineering; Engineering Design; Artificial Intelligence (incl. Robotics).; Biometrics